Controlling water transport in carbon nanotubes. (June 2017) - Goh, Kunli; Chen, Yuan
Graphical abstract: Highlights: Radius-dependent water slippage inside CNT measured using single CNT platform. Nanoconfinement induces curvature-dependent friction at the water-carbon interface. Electronic structures of CNT can control friction at the solid-liquid interface. Translating the potential of nanofluidic transport remains a challenge to be resolved. Abstract: Water transport inside carbon nanotubes (CNTs) shows a wealth of unique nanofluidic phenomena, which can be exploited as solutions for many global challenges. However, translating this potential into practical applications remains questionable to date. Recently, a work by Secchi and coworkers provides confirmatory evidence of radius-dependent water slippage inside an individual CNT. This article therefore puts into perspective two key takeaways, namely, nanoconfinement and electronic structures of CNT, as promising approaches to control ultrafast water transport inside CNTs.